PENGARUH ETIKA KERJA ISLAMI DAN KEPEMIMPINAN ISLAMI TERHADAP KINERJA KARYAWAN DI SMK AL MU’ALLIM KESUGIHAN - April Afrianto (NATUJA: Jurnal Ekonomi Syariah, 2025)
This study aims to determine the influence of Islamic work ethics and Islamic leadership on employee performance at SMK Al Mu'allim Kesugihan. This study uses a quantitative approach, with the population consisting of all employees at SMK Al Mu'allim Kesugihan, while the sample consists of 40 respondents, using saturated sampling technique. The data used in this study is primary data obtained through the distribution of questionnaires directly to respondents. The data analysis technique used in this study is multiple regression analysis using SPSS 26. The results of this study indicate that the test results (partial test) of Islamic work ethics with a significance value of 0.406 > 0.05, so it can be concluded that Islamic work ethics do not affect employee performance at SMK Al Mu'allim. Meanwhile, Islamic leadership has a positive influence with a partial test value and significance value of 0.001 < 0.05, so it can be concluded that Islamic leadership has a significant influence on employee performance at SMK Al Mu'allim Kesugihan. This study contributes to SMK Al Mu'allim Kesugihan in improving employee performance. The SPSS test results show that Islamic leadership has a significant effect (coefficient 0.404, sig. 0.001, Beta 0.520) on performance, while Islamic work ethics are not significant (coefficient 0.117, sig. 0.406). Both variables together explain 34.7% of performance variation (R²=0.347). The organization is advised to prioritize the development of Islamic leadership in order to improve optimal performance.